Communication for nurses : how to prevent harmful events and promote patient safety - Schuster, Pamela McHugh, 1953-; Nykolyn, Linda (F.A. Davis Co., 2010)
This exceptional book for nurses and nursing students guides the development of the comprehensive, professional communication skills to prevent errors that result in patient injuries and death. With a patient-safety focus, thorough coverage of communication and extensive, interactive ancillaries, it demonstrates how communication is tied to desired clinical outcomes. --Publisher description